The synthesis and antimicrobial activity of some new methyl N-arylthiocarbamates, dimethyl N-aryldithiocarbonimidates and 2-arylamino-2-imidazolines (vol 40, pg 687, 2005) - Servi, S; Genc, M; Gür, S; Koca, M (Elsevier France-Editions Scientifiques Medicales Elsevier, 2005)
[Abstract Not Available]